An investigation of boat tail helmet to reduce drag - Pathan, Khizar A.; Khan, Sher Afghan; Shaikh, Aadil N.; Pathan, Arsalan A.; Khan, Shahnawaz A. (Techno Press, 2021)
A helmet is a kind of shielding equipment used to shield the head from fatal injuries. The helmet experiences drag while moving at a certain velocity. The total drag on the helmet increases with an increase in velocity. The drag force at high velocity has a significant effect on the rider's neck and may result in cervical spondylosis. Now a day’s neck pain, neck sprain, spondylosis have become significant issues related to the human body. The reduction of drag on the helmet will be a boon for society, which will reduce the force on the neck. The decrease in drag is an essential field of study. The drag force can be reduced by various methods like coating on the surface, modifying the helmet's shape, etc. The study's purpose is to decrease drag on the helmet by improving the helmet's shape. The CFD analysis is carried out to find the best profile of the helmet and fineness ratio of the boat-tailed helmet to minimize drag. The CFD results are validated with the wind tunnel laboratory outcomes. Based on the findings, a considerable reduction in drag is accomplished at the velocity of 32.5 m/s.